2017
DOI: 10.1111/hsc.12528
|View full text |Cite
|
Sign up to set email alerts
|

Practitioners’ perspectives on community-based breast cancer survivorship care in Singapore: A focus group study

Abstract: With the long-term goal of optimising the delivery of breast cancer survivorship care in Singapore, we conducted a qualitative study to gather in-depth descriptions from community practitioners (general practitioners and community pharmacists) about their perceptions of community-based cancer survivorship care in Singapore. Sixteen participants (11 general practitioners and five community pharmacists) participated in four structured focus group discussions between August and November 2016. The focus group disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…First, we performed extensive literature review to develop the DA content. We we reviewed decisional needs from BCS’ and primary care HCPs’ perspectives based on two local qualitative studies [ 26 , 27 ]. Catering to reported informational needs, we designed the DA to address the following content areas: principles of cancer survivorship, roles of participating HCPs, clinical evidence of care models, care coordination strategies, and cost considerations.…”
Section: Methodsmentioning
confidence: 99%
“…First, we performed extensive literature review to develop the DA content. We we reviewed decisional needs from BCS’ and primary care HCPs’ perspectives based on two local qualitative studies [ 26 , 27 ]. Catering to reported informational needs, we designed the DA to address the following content areas: principles of cancer survivorship, roles of participating HCPs, clinical evidence of care models, care coordination strategies, and cost considerations.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the lack of empanelment could complicate the shared care model as multiple primary care practitioners may be involved which calls for greater coordination of care. 9 Considering these challenges, it would thus be critical to achieving the relevant changes in mindset from both the patients and primary care practitioners in which the value of shared care is clearly appreciated by all parties. In addition, it will be crucial to design the appropriate pricing and reimbursement structure to see through the successful uptake of such a shared care model.…”
Section: Current and Future Landscape Of Cancer Survivorship In Singamentioning
confidence: 99%
“…We previously conducted a pilot focus group study on private PCPs’ perspectives on community-based cancer survivorship care in Singapore and found that majority of private PCPs encounter very few cancer survivors in their practice ( 12 ). They reported barriers like patients’ lack of confidence in primary care, financial constraints, limited time and lack of empanelment.…”
Section: Introductionmentioning
confidence: 99%